2012
DOI: 10.1007/s00011-011-0414-6
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of acid-sensing ion channels protects articular chondrocytes from acid-induced apoptotic injury

Abstract: The data presented in this study provided some experimental evidence that blocking ASICs could protect acid-induced apoptotic injury to chondrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 35 publications
(40 reference statements)
4
39
0
Order By: Relevance
“…This signal transduction chain is in keeping with a recent publication (48) that reports a key role for L-type voltage-gated channels in osteoarthritis, evoked and aggravated by mechanical trauma. We consider it an appealing possibility that the chondrocytic Ca 2+ signal of cartilage traumatic injury impacts chondrocytes' cytoskeleton, energy homeostasis, apoptotic equilibrium, and inflammatory phenotype (15,(62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…This signal transduction chain is in keeping with a recent publication (48) that reports a key role for L-type voltage-gated channels in osteoarthritis, evoked and aggravated by mechanical trauma. We consider it an appealing possibility that the chondrocytic Ca 2+ signal of cartilage traumatic injury impacts chondrocytes' cytoskeleton, energy homeostasis, apoptotic equilibrium, and inflammatory phenotype (15,(62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the ASIC1a-specific blocker PcTX venom attenuated acid-induced articular chondrocyte damage [25]. Furthermore, blocking ASICs markedly decreased calpain and calcineurin expression levels as well as caspase-3/9 activity, and led to recovery of mitochondrial membrane potential via regulation of B-cell lymphoma-2 family gene expression in acid-induced chondrocytes [9,73]. A more recent study reported that interleukin-6 promotes acid-induced articular chondrocyte apoptosis to a significant extent by activating the JAK2/STAT3 and MAPK/NF-κB signaling pathways, resulting in upregulation of ASIC1a expression and function [4].…”
Section: Asics and Arthritismentioning
confidence: 99%
“…Information on the mechanisms that govern cell responses to mechanical stimuli in IVD is now emerging (38), and the presence of putative mechanoproteins in IVD cells has been recently reported (30). It must be noted that ASIC2 also serves as a mechanoprotein in certain cell types (11,15), and we have observed in this study that it is expressed in the AF and NP cells of healthy IVD and that its expression increased in degenerated IVD.…”
Section: Discussionmentioning
confidence: 83%
“…Blockade of ASICs attenuates articular cartilage destruction in adjuvantinduced arthritis by reducing the increase in intracellular [Ca(2+)]i, whereas ColI and aggrecan mRNA and protein expression were significantly increased (18). Blockade of ASICs in cultured chondrocytes significantly decreased the cell death by reducing acid-induced [Ca(2+)]i rises and inhibiting calpain and calcineurin expression, as well as caspase-3 activity (30). Furthermore, the ASIC blocker, amiloride, inhibited chondrocyte apoptosis in a dosedependent manner by regulating Bcl-2 family gene expression and activity of caspase 3/9 (31).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation